2020
DOI: 10.1088/1361-6404/ab9b3d
|View full text |Cite
|
Sign up to set email alerts
|

Entropy uniqueness determines temperature

Abstract: A thermometer is a temperature proxy, usually with a fixed number of parameters. When a nearly ideal gas or a similarly simple system is not available, the determination of a temperature scale is difficult, and has been subject to debate. Entropy uniqueness, due to Clausius, provides a fundamental theoretical criterion to answer this question. By measuring the heat flow dQ around a grid in p–V space, with M elemental areas, one can test a proposed temperature scale Tn by computing , the rms deviation, from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…With a specific dispute between two distinguished low temperature physicists in mind, the author recently considered [1], for a given region of p-v (pressure-volume) space, how to tell which of two temperature scales is preferable. It was shown that minimizing an rms entropy deviation, based on measuring heat flow into the system dQ m and a trial temperature scale T (with an agreed-upon number of parameters), can determine the parameters and thus determine the temperature scale.…”
Section: Addendummentioning
confidence: 99%
See 1 more Smart Citation
“…With a specific dispute between two distinguished low temperature physicists in mind, the author recently considered [1], for a given region of p-v (pressure-volume) space, how to tell which of two temperature scales is preferable. It was shown that minimizing an rms entropy deviation, based on measuring heat flow into the system dQ m and a trial temperature scale T (with an agreed-upon number of parameters), can determine the parameters and thus determine the temperature scale.…”
Section: Addendummentioning
confidence: 99%
“…If dQ m can be measured more accurately than P m , then temperature can be determined more accurately using dQ m . (One can imagine a space or deep sea probe whose temperature sensor has malfunctioned, and one is forced to measure temperature in an expected manner, such as proposed in [1].) However, any temperature-dependent property P m can be refined using an rms deviation method to find a dimensionless correction factor G, so that the corrected P m satisfies P = P m G. (G can depend on p and v.) In this way one can improve the accuracy of measurements of P m to make their accuracy comparable to those of dQ m , and thus dQ m -derived temperature measurements.…”
Section: Addendummentioning
confidence: 99%